Metallothermy in the cast iron “out of the furnace treatment ”process - Stanislaw Borkowski (Communications - Scientific letters of the University of Zilina, 2000)
Production of high-quality cast irons in a batch production is topical current problem. Existing technologies of melting cast iron are not very progressive. The basic theoretical knowledges of obtaining of alloyed cast iron (Cr, Ti) by using metalothermy are presented in this work. The oxides are sources of this elements. The metalothermy treatment process is running without decrease of liquid metal temperature, comes to increase of quantity addition elements and reduction of quantity of carbon and sulphur.